NMR profiling clarifies the characterization of Finnish honeys of different botanical origins. (August 2016) - Kortesniemi, Maaria; Slupsky, Carolyn M.; Ollikka, Tarja; Kauko, Lassi; Spevacek, Ann R.; Sjövall, Olli; Yang, Baoru; Kallio, Heikki
Abstract: The Finnish varietal honeys are valued specialty foods with unique characteristics, owing to their botanical origin. 1 H NMR metabolomics was applied to examine the compositional differences and origin-related markers of naturally complex boreal honeys (buckwheat, clover, dandelion, heather, Himalayan balsam, honeydew, linden, lingonberry, multifloral). Special focus was on the metabolites in aqueous samples. Chloroform extracts of selected samples were also analyzed for additional metabolic evidence. Qualitative profiling revealed 2-hydroxy-3-methylbutyric, 2-hydroxy-3-methylpentanoic, 3-methyl-2-oxopentanoic and 4-methyl-2-oxopentanoic acids as specific markers for dandelion ( Taraxacum spp.) honeys. Full discrimination of buckwheat, dandelion, heather, and honeydew honeys was achieved with principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). Melezitose, glucose, and fructose explained 83% of the variation in the PCA. The OPLS-DA loadings highlighted the discriminatory effect of the origin-specific non-saccharide metabolites. This study is a platform for a national honey library and analysis service. The results will facilitate and rationalize the characterization and quality control of the boreal varietal honeys. Graphical abstract: Highlights: First report on 1 H NMR metabolomics of Finnish varietal honeys Full discrimination of buckwheat, dandelion, heather, and honeydew honeys Fingerprints related to botanical origin revealed through qualitative profiling. Novel markers suggested for dandelion honeys.